Flora of community managed forests of Palpa district, western Nepal - Shrestha, Pratiksha; Chaudhary, Ram Prasad; Shrestha, Krishna Kumar; Dangol, Dharma Raj (Journal of Natural History Museum, 2018)
Floristic diversity is studied based on gender in two different management committee community forests (Barangdi-Kohal jointly managed community forest and Bansa-Gopal women managed community forest) of Palpa district, west Nepal. Square plot of 10m×10m size quadrat were laid for covering all forest areas and maintained minimum 40m distance between two quadrats. Altogether 68 plots (34 in each forest) were sampled. Both community forests had nearly same altitudinal range, aspect and slope but differed in different environmental variables and members of management committees. All the species present in quadrate and as well as outside the quadrate were recorded for analysis. There were 213 species of flowering plant belonging to 67 families and 182 genera. Barangdi-Kohal JM community forest had high species richness i.e. 176 species belonging to 64 families and 150 genera as compared to Bansa-Gopal WM community forest with 143 species belonging to 56 families and 129 genera. According to different life forms and family and genus wise jointly managed forest has high species richness than in women managed forest. Both community forest are banned for fodder, fuel wood and timber collection without permission of management comities. There is restriction of grazing in JM forest, whereas no restriction of grazing in WM forest.